ANALISIS PENGGUNAAN GADGET TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIA 4-5 TAHUN DI DESA JETAK KECAMATAN SINGOROJO KABUPATEN KENDAL - Sayekti, Dewi; D.S., Anita Chandra; Karmila, Mila (Universitas PGRI Semarang, 2022)
This study aims to describe how the use of gadgets in the development of psychosocial development of children aged 4-5 years in Jetak Village, Singorojo District, Kendal Regency. The method in this research is qualitative. Data collection techniques using interviews, observation and documentation. The data were analyzed by describing descriptively according to the existing facts. Using data reduction methods, display data and conclusions. The results of this study concluded that in Jetak Hamlet, Kedungsari Village, early childhood children are familiar with gadgets, especially during the covid 19 pandemic, children study at home so that the intensity of children holding gadgets becomes more. This is very influential on the child's psychosocial behavior, this influence can be a positive influence or a negative influence. The negative impact is that they are less enthusiastic in learning, children play more games or watch YouTube because it is a mandatory entertainment in the midst of school boredom that cannot meet face to face. Gadgets can also have a positive impact if there is supervision from parents. For children aged 4-5 years still obey the rules in the duration of using gadgets set by their parents even though sometimes parents scold their children.